1980
DOI: 10.1128/iai.27.3.995-1002.1980
|View full text |Cite
|
Sign up to set email alerts
|

Role of antibody and complement in the control of Encephalitozoon cuniculi infections by rabbit macrophages

Abstract: The capacity of mononuclear peritoneal macrophages to phagocytose Encephalitozoon cuniculi was tested in vitro. Normal rabbit serum or cell culture medium had little effect on the rate of removal of organisms by rabbit peritoneal macrophages. Treatment with immune rabbit serum or immune rabbit immunoglobulin G significantly (P less than 0.001) increased phagocytosis of E. cuniculi. Guinea pig complement was found to significantly (P less than 0.001) enhance the phagocytosis of antibody-treated E. cuniculi. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In vitro studies showed that some species of microsporidia, could replicate within parasitophorous vacuoles of the host cell due to an absence of fusion between the host cell lysosomes and the parasitophorous vacuole (Weidner 1975). Thioglycollate-ellicited lagomorph and murine peritoneal macrophages also support the growth and replication of E. cuniculi, but organisms opsonized with specific antibody are destroyed due to fusion of lysosomes with the parasitophorous vacuoles (Niederkorn & Shadduck 1980, Schmidt & Shadduck 1984. In addition, incubation of the murine elicited peritoneal murine (BALB/c) macrophages with sensitized T-enriched murine spleen-lymphocyte culture supernatants induced the macrophages to kill E. cuniculi (Schmidt & Shadduck 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that some species of microsporidia, could replicate within parasitophorous vacuoles of the host cell due to an absence of fusion between the host cell lysosomes and the parasitophorous vacuole (Weidner 1975). Thioglycollate-ellicited lagomorph and murine peritoneal macrophages also support the growth and replication of E. cuniculi, but organisms opsonized with specific antibody are destroyed due to fusion of lysosomes with the parasitophorous vacuoles (Niederkorn & Shadduck 1980, Schmidt & Shadduck 1984. In addition, incubation of the murine elicited peritoneal murine (BALB/c) macrophages with sensitized T-enriched murine spleen-lymphocyte culture supernatants induced the macrophages to kill E. cuniculi (Schmidt & Shadduck 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Coating live L. pneumophila with antibody, with or without complement, promotes fusion with lysosomes of a proportion of the bacterial phagosomes. Antibody has also been reported to promote fusion with lysosomes ofphagosomes containing M. tuberculosis (27), T. gondii (28), C. psittaci (6), and E. cuniculi (8).…”
Section: Discussionmentioning
confidence: 99%
“…While the link between Ab‐mediated protection, FcR engagement, and lysosomal localization of the pathogen has only been made for a few infectious agents, reports about other pathogens point toward this being a more general mechanism active against intracellular pathogens. For instance, Ab‐mediated targeting into lysosomes has been reported for the intracellular bacterium Rickettsia conorii and the protozoan parasite Encephalitozoon cuniculi ; both pathogens evade phagolysosomal fusion in the absence of specific Abs 83, 84. Furthermore, macrophage killing of Chlamydia was shown to be strongly enhanced in the presence of Abs 38.…”
Section: Opposing Signals: Fcr Triggering Versus Evasion Of Lysosomalmentioning
confidence: 96%